Different‐sized extracellular vesicles derived from stored red blood cells package diverse cargoes and cause distinct cellular effects. Issue 3 (8th February 2023) - Oh, Joo‐Yeun; Marques, Marisa B.; Xu, Xin; Li, Jindong; Genschmer, Kristopher R.; Phillips, Edward; Chimento, Melissa F.; Mobley, James; Gaggar, Amit; Patel, Rakesh P.
Abstract: Background: The formation of extracellular vesicles (EVs) occurs during cold storage of RBCs. Transfusion of EVs may contribute to adverse responses in recipients receiving RBCs. However, EVs are poorly characterized with limited data on whether distinct vesicles are formed, their composition, and potential biological effects. Study Design and Methods: Stored RBC‐derived EVs were purified using protocols that separate larger microvesicle‐like EVs (LEVs) from smaller exosome‐like vesicles (SEVs). Vesicles were analyzed by electron microscopy, content of hemoglobin, heme, and proteins (by mass spectrometry), and the potential to mediate lipid peroxidation and endothelial cell permeability in vitro. Results: SEVs were characterized by having an electron‐dense double membrane whereas LEVs had more uniform electron density across the particles. No differences in hemoglobin nor heme levels per particle were observed, however, due to smaller volumes, SEVs had higher concentrations of oxyHb and heme. Both particles contained antioxidant proteins peroxiredoxin‐2 and copper/zinc superoxide dismutase, these were present in higher molecular weight fractions in SEVs suggesting either oxidized proteins are preferentially packaged into smaller vesicles and/or that the environment associated with SEVs is more pro‐oxidative. Furthermore, total glutathione (GSH + GSSG) levels were lower in SEVs. Both EVs mediated oxidation of liposomes that were prevented by hemopexin, identifying heme as the pro‐oxidant effector. Addition of SEVs, but not LEVs, induced endothelial permeability in a process also prevented by hemopexin. Conclusion: These data show that distinct EVs are formed during cold storage of RBCs with smaller particles being more likely to mediate pro‐oxidant and inflammatory effects associated with heme.